Neuroprotective activity of new Δ3‐N‐acylethanolamines in a focal ischemia stroke model. Issue 1 (9th November 2021) - Shirazi, Rahau S.; Vyssotski, Mikhail; Lagutin, Kirill; Thompson, Dion; MacDonald, Christa; Luscombe, Vincent; Glass, Michelle; Parker, Kim; Gowing, Emma K.; Williams, D. Bradley G.; Clarkson, Andrew N.
Abstract: N‐acylethanolamines (NAE, also called ethanolamides) are significant lipid signaling molecules with anti‐inflammatory, pain‐relieving, cell‐protective, and anticancer properties. Here, we present the use of a hitherto unreported group of Δ3‐NAE and also some Δ4‐ and Δ5‐NAE, in in vitro and in vivo assays to gain a better understanding of their structure–bioactivity relationships. We have developed an efficient synthetic method to rapidly produce novel unlabeled and 13 C‐labeled Δ3‐NAE (NAE‐18:5n‐3, NAE‐18:4n‐6) and Δ4‐NAE (NAE‐22:5n‐6). The new NAE with shorter carbon backbone structures confers greater neuroprotection than their longer carbon backbone counterparts, including anandamide (Δ5‐NAE‐20:4n‐6) in a focal ischemia mouse model of stroke. This study highlights structure‐dependent protective effects of new NAE following focal ischemia, in which some of the new NAE, administered intranasally, lead to significantly reduced infarct volume and improved recovery of limb use. The relative affinity of the new NAE toward cannabinoid receptors was assessed against anandamide, NAE‐22:6n‐3 and NAE‐20:5n‐3, which are known cannabinoid receptor ligands with high‐binding constants. Among the newly synthesized NAE, Δ4‐NAE‐22:5n‐6 shows the greatest relative affinity to cannabinoid receptors hCB1 and hCB2, and inhibition of cyclic adenosine monophosphate activity through hCB2 compared to anandamide.